Joe Hustle : a novel - Lange, Richard, 1961- (Little Brown & Company, 2024)
Joe Hustle is a survivor. A Gulf War vet and ex-con always one stumble away from catastrophe, he manages to scrape together enough money from various jobs to eke out a precarious existence on the darker fringes of Los Angeles. When he meets Emily, the black-sheep daughter of a wealthy family, the two spark an instant connection--she seems like the best thing to happen to him in a while. But their whirlwind romance is put to the test when what starts out as a simple favor for a friend leaves Joe homeless, unemployed, and on the wrong side of a vengeful drug dealer. An impulsive offer to go on a road trip with Emily promises to take them out of harm's way--but may only lead to more chaos.